Umu Bakeshop / Farah Nabilah Noor Hisham - Noor Hisham, Farah Nabilah Noor Hisham (2022)
The idea to open and online cake shop with the concept of a family, business (home made) was not something easy. Thanks to the strong support from the husband and family as well as the hard work of oneself to gain knowledge in the field of cake and bread making, finally the family's dream can be realized. Umu bakeshop products are halal Muslim products and meet current taste that always care about cleanliness and product quality. Rebranding Umu bake shop is not something easy but i have manage to make the service more appealing and suitable for any age to enjoy their cake This client has great potentials to expand their services through engaging its designs and advertisement with consumers around Malaysia.